2018
DOI: 10.21829/abm126.2019.1384
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias en morfometría y germinación de semillas de Croton guatemalensis (Euphorbiaceae), procedentes de poblaciones silvestres de la Selva Zoque, Chiapas, México

Abstract: Antecedentes y Objetivos: Croton guatemalensis es una especie nativa que tiene diversos usos locales y juega un papel importante en la medicina tradicional de los habitantes de las comunidades campesinas de la Selva Zoque, Chiapas, México. Actualmente, la especie se encuentra protegida por la NOM-059-SEMARNAT-2010 bajo “Protección Especial”. El presente trabajo tuvo como objetivos evaluar la morfometría, viabilidad, sanidad y germinación de semillas recolectadas en poblaciones silvestres de cuatro Áreas Natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Additionally, a habitat suitability layer was created specifically for C. guatemalensis. To build this layer, information about the reproductive phenology and physiology of the species reported by Pozo-Gómez et al (2019, 2020 was used. This included ideal conditions for reproductive effort (number and size of fruits), reproductive potential (number and size of seeds per fruit, health and viability of seeds), and reproductive success (germination rate).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a habitat suitability layer was created specifically for C. guatemalensis. To build this layer, information about the reproductive phenology and physiology of the species reported by Pozo-Gómez et al (2019, 2020 was used. This included ideal conditions for reproductive effort (number and size of fruits), reproductive potential (number and size of seeds per fruit, health and viability of seeds), and reproductive success (germination rate).…”
Section: Methodsmentioning
confidence: 99%
“…This included ideal conditions for reproductive effort (number and size of fruits), reproductive potential (number and size of seeds per fruit, health and viability of seeds), and reproductive success (germination rate). For the construction of the habitat suitability layer, we compile all the occurrences reported by Pozo-Gómez et al (2019, 2020, which were filtered, keeping only those where they reported the maximum values of reproductive effort, reproductive potential, and reproductive success. Only 20 occurrences that included these attributes were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such is the case of Copalchí (Croton guatemalensis), a species whose distribution goes from southern Mexico to Panama, acclimated in South America and the Caribbean at altitudes of up to 1700 meters above sea level (Cardenas, 2006). In, Mexico this native species is considered to have special protection under the Mexican legislation (Secretaría de Medio Ambiente y Recursos Naturales [Semarnat], 2010); it is a species used by local communities as medicine, for use as live fences and poles, as firewood, for the extraction of wood, honey, fodder, or for construction and manufacturing of work tools (Pozo-Gómez, Orantes-García, Rioja-Paradela, Moreno-Moreno, & Farrera-Sarmiento, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the importance of C. guatemalensis in the Zoque Tropical Forest Biological Corridor, its current exploitation is carried out in wild populations without adequate forest management, and in addition there are no scientific studies on its ecophysiology that allow to generate suitable protocols for its reproduction, propagation and proper management (Pozo-Gómez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%